Export competitiveness of groundnut: A state wise analysis: EXPORT COMPETITIVENESS OF GROUNDNUT: A STATE WISE ANALYSIS - MURLIDHAR MEENA; K A KHUNT; H N MEENA; H T KHORAJIYA (Journal of Oilseeds Research, 2018)
The export of agricultural commodities became competitive in post-WTO period as a result of increased interaction of world economies. Therefore, it is relevant to check competitiveness of groundnut export from India. Export competitiveness was assessed for major groundnut growing states viz., Andhra Pradesh, Gujarat, Karnataka, Maharashtra and Tamil Nadu using Policy Analysis Matrix from 1996-97 to 2013-14. Groundnut was found export competitive in all the states except in Karnataka in almost all the years. The values of Nominal protection coefficient (NPC), Effective protection coefficient (EPC) and Effective subsidy coefficient (ESC) measured less than unity, indicating the export worthiness. Domestic resource cost ratio (DRCR) values were found below one indicating the efficient utilisation of domestic resources in this crop. Social profit was measured positive throughout years indicating the positive social welfare in producing and exporting groundnut from these states. Total policy transfer measured negative in all the states indicating that this crop is generating resources to the state economy of all the major groundnut producing states. The export competitiveness of groundnut from India was found to improve over years during the study period. Therefore, government support and promotional activities can help to boost groundnut export from India.